2016
DOI: 10.1038/tp.2016.236
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma levels of circulating cell-free mitochondrial DNA in suicide attempters: associations with HPA-axis hyperactivity

Abstract: Preclinical data suggest that chronic stress may cause cellular damage and mitochondrial dysfunction, potentially leading to the release of mitochondrial DNA (mtDNA) into the bloodstream. Major depressive disorder has been associated with an increased amount of mtDNA in leukocytes from saliva samples and blood; however, no previous studies have measured plasma levels of free-circulating mtDNA in a clinical psychiatric sample. In this study, free circulating mtDNA was quantified in plasma samples from 37 suicid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
80
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 58 publications
5
80
2
Order By: Relevance
“…248 Also, OS and neuroinflammation play a critical role in the occurrence of fatigue in MS. 80 HPA-axis dysfunction has been implicated in MS. 249 Research indicates that mitochondria DNA damage is strongly associated with HPA-axis alteration and negative feedback. 250 Evidence suggests that mitochondria play a role in HPA axis and influence the body's response to psychological stress both at the cellular and global levels. 251 Also, activation of the HPA axis induces OS 252 and OS could result in HPA axis alteration.…”
Section: Other Factorsmentioning
confidence: 99%
“…248 Also, OS and neuroinflammation play a critical role in the occurrence of fatigue in MS. 80 HPA-axis dysfunction has been implicated in MS. 249 Research indicates that mitochondria DNA damage is strongly associated with HPA-axis alteration and negative feedback. 250 Evidence suggests that mitochondria play a role in HPA axis and influence the body's response to psychological stress both at the cellular and global levels. 251 Also, activation of the HPA axis induces OS 252 and OS could result in HPA axis alteration.…”
Section: Other Factorsmentioning
confidence: 99%
“…In addition to its elevation in injury and severe health conditions, higher ccf-mtDNA levels have been found in suicide attempters 18 and patients with major depressive disorder 19 , representing crosssectional evidence for a possible link between psychological states and ccf-mtDNA. Activation of the hypothalamic-pituitary-adrenal (HPA)-axis and the peripheral release of glucocorticoids is a primary neuroendocrine mediator of physiological responses to psychological stress 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the hypothalamic-pituitary-adrenal (HPA)-axis and the peripheral release of glucocorticoids is a primary neuroendocrine mediator of physiological responses to psychological stress 20 . Interestingly, alterations of the HPA axis may also be implicated in the regulation of ccf-mtDNA levels in humans 18 and mtDNA gene expression in animals 21 . However, whether psychological stress (in the absence of physical injury) or glucocorticoid signaling induce ccf-mtDNA release has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, more recent studies reported that mood disorders are more frequent in maternal relatives of children with mitochondrial diseases, compared with their paternal relatives, or compared with maternal relatives of the children with other metabolic diseases (Grigoroiu-Serbanescu et al, 1998; Kato, 2001; Linnane et al, 1989). In this argument, some authors reported an increased mtDNA- copy number in peripheral cells and plasma in depressed (Cai et al, 2015; Nicod et al, 2016) and suicidal (Lindqvist et al, 2016) subjects. Finally, several mitochondrial encephalomyopathies are characterized by a high prevalence of bipolar disorder and depression (Kato, 2001).…”
Section: Introductionmentioning
confidence: 99%